Diet Quality, Nutritional Status, and Haemoglobin Level of Female Adolescent Athletes in Endurance and Non Endurance Sports - Nisa Nur Isnaini Andari; Fillah Fithra Dieny; A.Fahmy Arif Tsani; Deny Yudi Fitranti; Nurmasari Widyastuti (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
Background: Based on the duration and intensity of the exercise, sports can b classified into two types: endurance and non endurance (strength and power). Endurance sports is a high risk sport with low diet quality, nutritional status (body mass index (BMI) and body fat percentage), and haemoglobin level. Objectives: The aimed of this study is to analyze the differences of diet quality, nutritionl status, and haemoglobin level of female adolescent athletes in endurance and non endurance sports. Methods: An observational study with a cross-sectional design was conducted on 23 endurance athletes and 21 non endurance athletes in BBLOP Central Java, UNNES swimming and athletic sports club, and Salatiga atlhetic sports club. Subjects were selected by purposive sampling. BMI and body was measured by Bioelectrical Impedance Analysis (Tanita DC-360). Haemoglobin level was assessed by cyanmethemoglobin method. Diet quality was measured by semi quantitative food frequency questionnaire (SQ-FFQ) and diet quality index-international (DQI-I) form. Data was analyzed by independent t-test and Mann-Whitney. Results: The majority of nutritional status based on BMI and perventage body fat in endurance and non endurance athlete were normal. About 9,5% of non endurance athlete had anemia. There were significant difference in diet quality (p=0,029) and variety of protein source, iron, vitamin C, and empty calorie foods intake (p<0,001; p=0,028; p=0,045; p<0,001) of endurance and non endurance athletes, but no significant difference in body fat percentage (p=0,573) and haemoglobin level (p=0,714). Conclusion: There were significant difference on diet quality, variety of protein source, iron, vitamin C, and empty calorie foods intake between endurance and non endurance athletes.